Visualizing Language: A Canva-Based Digital Comic for Enhancing Arabic Learning in Elementary Education - Annada Khikmatul 'Alawiyyah; Nurul Murtadho; Nurhidayati (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study aims to develop and evaluate the effectiveness of digital comic-based learning media as an innovative tool to improve Arabic learning outcomes at PSM Islamic Elementary School Tulungagung. Using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation), this research involved students from grades I to VI. The media was developed through Canva and integrated with QR Code technology to create an interactive, enjoyable, and accessible learning experience. The novelty of this study lies in the integration of visual comic media with QR Codes in Arabic language instruction at the Madrasah Ibtidaiyyah level. It not only focuses on cognitive outcomes but also assesses the media’s impact on students’ motivation and engagement through evaluation tools based on cognitive, affective, and psychomotor domains. The digital comic supports a meaningful understanding of vocabulary and context in Arabic. The results showed a significant improvement in student learning outcomes, with average scores rising from 80.24 (pre-test) to 92.71 (post-test). Additionally, students demonstrated increased interest, motivation, and active participation during the learning process. Digital comics proved to be an effective and feasible learning alternative, especially for teaching vocabulary and contextual understanding. This study provides pedagogical implications for Arabic language teaching in elementary education by promoting QR-integrated comics as engaging learning media. It is recommended that teachers and schools adopt such digital tools in classroom instruction. Future research may expand this media to different educational levels and subject areas. ملخص تهدف هذه الدراسة إلى تطوير وتقييم فعالية وسائل التعلم الرقمية القائمة على الهزلي الرقمي كأداة مبتكرة لتحسين نتائج تعلم اللغة العربية في مدرسة سبيل المتقين الإسلامية الابتدائية في تولونج أغونج. باستخدام نموذج التطوير ADDIE (التحليل، التصميم، التطوير، التنفيذ، التقويم)، شملت هذه الدراسة طلابًا من الصف الأول إلى السادس. تم تطوير الوسائط من خلال كانفا ودمجها مع تقنية QR Code لخلق تجربة تعليمية تفاعلية وممتعة وسهلة الوصول. تكمن جدة هذه الدراسة في دمج الوسائط المرئية المصورة مع رموز QR في تدريس اللغة العربية على مستوى المدارس الابتدائية الإسلامية. ولا تركز الدراسة على النتائج المعرفية فحسب، بل تقيّم أيضًا تأثير الوسائط على تحفيز الطلاب ومشاركتهم من خلال أدوات تقييم تستند إلى المجالات المعرفية والعاطفية والحركية. تدعم الهزلي الرقمي الفهم الهادف للمفردات والسياق في اللغة العربية. أظهرت النتائج تحسنًا كبيرًا في نتائج تعلم الطلاب، حيث ارتفع متوسط الدرجات من 80.24 (قبل الاختبار) إلى 92.71 (بعد الاختبار). ثم أظهر الطلاب اهتمامًا متزايدًا ودافعًا ومشاركة نشطة خلال عملية التعلم. أثبتت الهزلي الرقمي أنها بديل تعليمي فعال وممكن، خاصة لتعليم المفردات وفهم السياق. توفر هذه الدراسة آثارًا تربوية لتعليم اللغة العربية في التعليم الابتدائي من خلال الترويج للهزلي الرقمي المدمجة مع QR كوسيلة تعليمية جذابة. يوصى بأن يتبنى المعلمون والمدارس هذه الأدوات الرقمية في التدريس داخل الفصول الدراسية. قد توسع الأبحاث المستقبلية هذه الوسيلة إلى مستويات تعليمية ومجالات دراسية مختلفة.